Importance of assessing the impact of combined lifestyle factors related to periodontitis in costa ricans = La importancia de evaluar el impacto de la combinación de factores de estilos de vida relacionados con la periodontitis en costarricenses - Rodríguez Callaci, María Fernanda 2000-; Ramírez, Karol 1977- (2025)
Periodontal disease is an infectious and inflammatory disease, which is characterized by the destruction of tooth supporting tissues: root cementum, periodontal ligament and alveolar bone. Dental biofilm or plaque is the etiological risk factor for gum disease. There are a variety of risk factors that may contribute the onset and progression of periodontitis. Modifiable risk factors are habituated risk factors that can be changed by adjusting behavioral attitudes. These adjustments minimize the possibility of chronic disease occurrence. Thus, it becomes important, to identify individual modifiable factors such as lifestyle factors, which could influence the severity and higher risk of progression of periodontitis. Diet, physical activity, stress levels, sleep quality, smoking, and alcohol consumption, in relation to periodontal disease have been studied individually. Little is known about the combined effect of these health-related lifestyle patterns related to health and periodontal status. Studying the combination of lifestyle factors is recommended to establish an adequate management and treatment plan of patients with periodontitis. Costa Ricans present a unique pattern of sociodemographic, ethnic, cultural diversity, and lifestyle factors. Assessing these variables in different populations are a priority, to prevent and treat chronic diseases, such as periodontitis.
La enfermedad periodontal es una enfermedad infecciosa e inflamatoria, que se caracteriza por la destrucción de los tejidos de soporte del diente: cemento radicular, ligamento periodontal y hueso alveolar. El biofilm dental o placa es el factor de riesgo etiológico de la enfermedad de las encías. Existe una variedad de factores de riesgo que pueden contribuir a la aparición y progresión de la periodontitis. Los factores de riesgo modificables son factores de riesgo habituales que pueden cambiarse ajustando las actitudes conductuales. Estos ajustes, minimizan la posibilidad de que se produzcan enfermedades crónicas. Por lo tanto, resulta importante identificar factores modificables individuales, como los factores de estilo de vida, que podrían influir en la gravedad y el mayor riesgo de progresión de la periodontitis. Se han estudiado individualmente la dieta, la actividad física, los niveles de estrés, la calidad del sueño, el tabaquismo y el consumo de alcohol, en relación con la enfermedad periodontal. Se sabe poco, sobre el efecto combinado de estos patrones de estilo de vida relacionados con la salud y el estado periodontal. Se recomienda estudiar la combinación de factores del estilo de vida para establecer un adecuado plan de manejo y tratamiento de los pacientes con periodontitis. Los costarricenses presentan un patrón único de factores sociodemográficos, étnicos, de diversidad cultural y de estilos de vida. Evaluar estas variables en diferentes poblaciones, son una prioridad para prevenir y tratar enfermedades crónicas, como la periodontitis.
En revista Odóvtos, vol. 27, no.1 (enero-abril 2025)
Descripción basada en el contenido visto el 26 de marzo, 2025
También disponible en formato HTML y EPUB